SUCCESSFUL DELIVERY OF HYDROCEPHALIC FOAL THROUGH FETOTOMY IN A MARE - Kumar, Ajeet; GHUMAN, S P S; HONPARKHE, M (The Indian Journal of Animal Reproduction, 2010)
A case of successful pervaginal delivery of hydrocephalic foal through partial fetotomy and byrelieving the fluid from enlarged head has been reported.
Keywords: Foal; Dystocia; Fetotomy; Hydrocephalus